Gender dynamics of irrigation: Making way for women leaders in Western Terai, Nepal - Khadka, Manohara; Koirala, Sanju; Adhikari, Manju; Yangkhurung, Jigyasha Rai (CGIAR System Organization, 2023)
In the Western Terai region of Nepal, women farmers who irrigate their fields experience a disparity. On the one hand, women are largely responsible for the day-to-day running of irrigation systems; on the other hand, these same farmers are often excluded from planning and management decisions – particularly those made by water user associations (WUAs).